Determination of fundamental astrophysical properties of poorly known galactic open clusters from Washington photometry - Marcionni, N. (2015)
Abstract: As a complement to our photometric studies on southern open clusters (OCs), we present preliminary results obtained from a photometric analysis in the Washington system C and T1 passbands of some poorly known Galactic OCs. The observations were made using the CTIO 0.9 m telescope. Basically, we determine reddening, distance, and age of the observed objects. The present results are part of a major project which aims to characterize almost a hundred OCs observed and analyzed in a homogeneous way.